2021
DOI: 10.1007/s10098-021-02144-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing rainwater quality treated via a green roof system

Abstract: The shortage of water worldwide is increasingly worrying. Studies in the field suggest that sustainable water resource management via water recycling is fundamental to alleviate the issue. The use of rainwater is an important alternative source that must be considered, mainly, in the water crisis facing the planet. When integrated with the concept of green roofs, the capturing and treatment of rainwater in these structures becomes an even more ecological and sustainable practice. The water drained by the roof … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Se destaca la capacidad de reducir la huella de carbono y ser eficiente al reutilizar residuos de construcción en la composición del sustrato (Kuoppamäki y Lehvävirta, 2016; Xue y Farrell, 2020), así como la necesidad de estudios detallados sobre el impacto de los materiales en la calidad del agua de lluvia (Baryła et al, 2018;Sá et al, 2022) y los acv (Gargari et al, 2016;Shafique et al, 2020) respaldan la adopción de materiales alternativos. Sin embargo, aún no se han documentado ejemplos claros que muestren una integración efectiva de la economía circular en la optimización de los techos verdes.…”
Section: Resultados Y Discusiónunclassified

Economía circular mexicana

Castillo González,
De Medina Salas,
Giraldi Díaz
et al. 2024
“…Se destaca la capacidad de reducir la huella de carbono y ser eficiente al reutilizar residuos de construcción en la composición del sustrato (Kuoppamäki y Lehvävirta, 2016; Xue y Farrell, 2020), así como la necesidad de estudios detallados sobre el impacto de los materiales en la calidad del agua de lluvia (Baryła et al, 2018;Sá et al, 2022) y los acv (Gargari et al, 2016;Shafique et al, 2020) respaldan la adopción de materiales alternativos. Sin embargo, aún no se han documentado ejemplos claros que muestren una integración efectiva de la economía circular en la optimización de los techos verdes.…”
Section: Resultados Y Discusiónunclassified

Economía circular mexicana

Castillo González,
De Medina Salas,
Giraldi Díaz
et al. 2024
“…Zhang et al [62] found that in strains of Escherichia coli and Pseudomonas aeruginosa, after exposure to UV radiation, cell membranes remained intact even at UV doses of 300 mJ/cm 2 . Moreover, dead cells are a source of additional portions of nutrients for living cells [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include low-impact development (LID) [7], sustainable urban drainage systems (SUDS) [8], water-sensitive urban design (WSUD) [9]. An important strategy in the WSUD system is to control the source of runoff to improve the quality of stormwater runoff and reduce the amount of water [10,11]. The installation of green roofs is considered to be the best management measure for reducing peak urban runoff and improving the quality of stormwater runoff [12,13].…”
Section: Introductionmentioning
confidence: 99%